(3GdahGFO GdefJNHI ef GdNhGU GdeLQHIs - (3CHh GdeYGdj YHO Gdedc Hf CHj GdYdGA, GHf RgQ GdeJWHH,J (B557 (3g` s
(3ChdgG (B:s
(3MQa GdBda TYQ GdEfSGf EPG HNQ Hg TF UaQg s
(3BNQgG (B:s
(3hjcJHg cdeGJ jbhe HgG GdEfSGf GdeUQhY ai COfg jJce HgG GdEfSGf Je GdcJGH HMeO Gddg hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs